Analisis Semiotika Iklan Ramadhan Gojek ‘#Mauramadhanfull’ dan Iklan Ramadhan Grab ‘#Grabinramadhan’ pada Layanan Transportasi Daring di Indonesia - Raffa, Muhammad; Firdaus, Iqbal; Wijaya, Mario Eka; Jacob, Louris; Rio, Avilla (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article presents a comparative semiotic analysis of Ramadhan campaign advertisements from two Southeast Asian technology giants, Gojek (“#Mauramadhanfull”) and Grab (“#Grabinramadhan”). Employing Roland Barthes’ theoretical framework: denotation, connotation, and myth. This research dissects how both brands construct different meanings and ideologies within the unique cultural and commercial landscape of Ramadhan in Indonesia. The analysis finds that Gojek constructs a “Myth of Facilitated Piety,” positioning itself as an integral enabler for achieving a holistic and spiritually fulfilling Ramadan experience. Conversely, Grab constructs a “Myth of Instant Consumerist Fulfillment” through a meta-humorous narrative that deconstructs traditional advertising and promotes its platform as a magical solution for immediate desire fulfillment. This paper concludes that the competition between Gojek and Grab extends beyond service offerings. It is a semiotic battle to define the role of technology in contemporary religious practice, reflecting and actively shaping the intersection of tradition, consumerism, and digital life in Indonesia.